2009
DOI: 10.1177/1073191109356544
|View full text |Cite
|
Sign up to set email alerts
|

The Validity of the Psychopathic Personality Inventory—Revised in a Community Sample

Abstract: Research on the Psychopathic Personality Inventory-Revised (PPI-R; Lilienfeld & Widows, 2005) initially revealed two factors: FearlessDominance, and Self-Centered Impulsivity. This study examined the validity of the PPI-R factors in a community sample (N=675). First, confirmatory factor analyses did not support the two-factor structure. Second, the PPI-R factors showed good convergent and discriminant validity with two other selfreport measures of psychopathy, i.e. the Youth Psychopathic Traits Inventory (YPI;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
75
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 60 publications
(107 reference statements)
7
75
1
Order By: Relevance
“…However, the items (e.g., "I usually feel calm when other people are scared") are not youth-specific, and the few instances where youth-specific terms are used, the item is rephrased such that it is also applicable to adults (e.g., "If I won a lot of money in the lottery I would quit school or work and just do things that are fun"). It is therefore that the YPI has also appeared reliable and valid in undergraduate samples (e.g., Sherman, Lynam & Heyde, 2014) and in adults (e.g., Uzieblo et al, 2010), and that its factors showed adequate internal consistency in the present study. Concerning the interpretation of our results, one has to be aware that the YPI does not explicitly assess antisocial or criminal behavior, preventing us from to examine whether and to what extent the relation between the behavioral-lifestyle facet of psychopathy and attachment is related to antisociality.…”
Section: Discussionsupporting
confidence: 52%
“…However, the items (e.g., "I usually feel calm when other people are scared") are not youth-specific, and the few instances where youth-specific terms are used, the item is rephrased such that it is also applicable to adults (e.g., "If I won a lot of money in the lottery I would quit school or work and just do things that are fun"). It is therefore that the YPI has also appeared reliable and valid in undergraduate samples (e.g., Sherman, Lynam & Heyde, 2014) and in adults (e.g., Uzieblo et al, 2010), and that its factors showed adequate internal consistency in the present study. Concerning the interpretation of our results, one has to be aware that the YPI does not explicitly assess antisocial or criminal behavior, preventing us from to examine whether and to what extent the relation between the behavioral-lifestyle facet of psychopathy and attachment is related to antisociality.…”
Section: Discussionsupporting
confidence: 52%
“…Related to the Emotionality factor, Fearfulness, Anxiety, and Dependence facets were negatively correlated to the DAPTQ, but not sentimentality. Multiple studies identified a link between PPI-I and resilience to fear and anxiety, alongside low emotional reactivity (López, Poy, Patrick, & Moltó, 2013;Uzieblo et al, 2010). Considering the strong association between PPI-I and the DAPTQ, these results support the capacity of the DAPTQ to assess adaptive traits closely related to the psychopathic personality (Durand, in press).…”
Section: Discussionsupporting
confidence: 65%
“…To the extent that low faking good scores reflect real true aspects of psychopathy, controlling for faking good would actually reduce the relation between psychopathy and the criterion measures. For this purpose, we performed a secondary analysis on the data from Uzieblo et al (2010). We examined whether controlling for faking good increased -as predicted by the response bias hypothesisor decreased -as predicted by the true variance in psychopathy hypothesis -the expected positive association between psychopathy and antisocial behavior.…”
mentioning
confidence: 99%